Association of pain and frailty in older adults with Gonarthrosis referred to a university hospital in Türkiye - Azize Aydemir; Dilek Yidirim Gürkan; Murat Korkmaz; Muhammed Sarikaya (Journal of Research Development in Nursing and Midwifery)
Background: Gonarthrosis (GA) is a chronic degenerative disease. This study aimed to determine the frailty level of patients with GA aged 65 and over and to investigate the effect of pain on frailty. Methods: The population of this cross-sectional study consisted of patients and their relatives who applied to the orthopedics and traumatology outpatient clinic of a university hospital for examination, follow-up and treatment from October 1, 2021, to January 31, 2022. The study was completed with 160 elderly people aged 65 years and over. Data were collected using Personal Information Form, Tilburg Frailty Indicator (TFI), Get Up and Go Test (GGT), and Geriatric Pain Scale (GPS). Simple descriptive statistics, as well as correlation and multiple linear regression analysis, were used to analyze the data using SSPS 20. The significance level was set at p <0.05. Results: In this study, 45.6% of the participants were found to have moderate pain (52.42±12.40), 70% were frail (7.58±2.13), and 36.9% had a fall risk (17.15±7.57). The mean TFI (7.48±2.38), GGT (12.01±6.16), and GPS (71.37±14.20) scores of the participants with GA were significantly higher than those without GA. The frailty scores of the participants with severe pain and a high risk of falling were significantly higher (p <0.05). Moreover, the pain severity of the participants accounted for 47.7% of the frailty level. According to our regression model, the variable affecting the severity of major pain was GA stage IV (p=0.000), which increased pain by 3.260 (2.456-3.944) times. Conclusion: The study provides ample evidence supporting the potential importance of pain severity assessment and pain management to prevent frailty in patients with GA aged 65 and over.